2019
DOI: 10.1088/1755-1315/298/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Dyes Production by Mixed Aspergillus and Paecilomyces and Its Coloring on Cotton Cloth

Abstract: The present study aimed to optimize dyes of mixed Aspergillus and Paecilomyces and to evaluate dyes of the fungi in coloring cotton cloth. Different initial pH values (3, 5, 7, and 9), temperatures (24, 27, and 30°C), carbon sources (lactose, glucose, and sucrose,) and nitrogen sources (monosodium glutamate, potassium nitrate, sodium nitrate, and yeast extract) of the medium related to dyes and biomass production; and they coloring on cotton cloth were analysed. The optimum culture conditions for the dyes prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Inoculation process was performed as our previous method (Suciatmih, 2019). Briefly, each five mycelial prints were inoculated into three different media (per liter of distilled water) separately: 1) mineral salt glucose (MSG) medium (Backer and Tatum, 1998) contained: 20 g glucose, 0.848 g NaNO3, 0.3 g KCl, 0.165 g MgSO4.7H2O, 0.1 g NaH2PO4, 0.04 g CaCl2.2H2O, 0.0057 g H3BO3, 0.005 g FeSO4.7H2O, 0.0044 g ZnSO4.7H2O, 0.0031 g MnSO4.H2O, 0.0025 g Na2MoO4.2H2O, 0.0004 g CuSO4.5H2O, and pH 6.0; 2) mineral salt glucose (MSG) medium (Cho et al, 2002) contained: 30 g glucose, 2 g yeast extract, 2 g peptone, 0.5 g MgSO4.7H2O, 0•46 g KH2PO4, 1 g K2HPO4, and pH 5; and 3) mineral salt sucrose (MSS) medium (Poorniammal et al, 2013) contained: 30 g sucrose, 3 g NaNO3, 0.5 g KCl, 1 g K2HPO4, 1 g MgSO4, and pH 6.…”
Section: Selection Of Culture Mediamentioning
confidence: 99%
See 3 more Smart Citations
“…Inoculation process was performed as our previous method (Suciatmih, 2019). Briefly, each five mycelial prints were inoculated into three different media (per liter of distilled water) separately: 1) mineral salt glucose (MSG) medium (Backer and Tatum, 1998) contained: 20 g glucose, 0.848 g NaNO3, 0.3 g KCl, 0.165 g MgSO4.7H2O, 0.1 g NaH2PO4, 0.04 g CaCl2.2H2O, 0.0057 g H3BO3, 0.005 g FeSO4.7H2O, 0.0044 g ZnSO4.7H2O, 0.0031 g MnSO4.H2O, 0.0025 g Na2MoO4.2H2O, 0.0004 g CuSO4.5H2O, and pH 6.0; 2) mineral salt glucose (MSG) medium (Cho et al, 2002) contained: 30 g glucose, 2 g yeast extract, 2 g peptone, 0.5 g MgSO4.7H2O, 0•46 g KH2PO4, 1 g K2HPO4, and pH 5; and 3) mineral salt sucrose (MSS) medium (Poorniammal et al, 2013) contained: 30 g sucrose, 3 g NaNO3, 0.5 g KCl, 1 g K2HPO4, 1 g MgSO4, and pH 6.…”
Section: Selection Of Culture Mediamentioning
confidence: 99%
“…After incubation with different treatments, the culture was passed through five layers of cheesecloth, and the filtrate was centrifugated at 8500 rpm for 20 min as performed previously (Suciatmih, 2019). The optical density of the filtrate was determined by spectrophotometre (Shimadzu) at 530 nm for quantifying the dyes (Suciatmih, 2019). The dyes' yield was calculated as OD units (UA530).…”
Section: Harvesting Of Dyementioning
confidence: 99%
See 2 more Smart Citations
“…Previous research reported that mixed Aspergillus and Paecilomyces produced 187A greyed-purple dye and could dye cloths (Suciatmih et al 2018;Suciatmih 2019;Suciatmih 2020), but its ability to paint pictures was untested. Using mixed fungi is intended to maintain the fungi's ability to produce dye.…”
Section: Introductionmentioning
confidence: 99%